A BNCC em diálogo com o conhecimento pedagógico do conteúdo (PCK) dos professores de matemática - Silva, Carla Martins da (2022)
In this thesis, we seek to appreciate the Pedagogical Content Knowledge of a group of teachers relating it to the competences/abilities foreseen by the National Common Curricular Base (BNCC), to guide the integral formation of students, based on the assumptions of the Theory of Shulman's (1987) Teachers' Knowledge. The methodological procedures of this study took place through a qualitative approach, whose corpus was analyzed through Discursive Textual Analysis (DTA). The thesis defended is “The Mathematics teacher obtains better results when he has understanding and ownership of the knowledge that organizes his pedagogical content knowledge, because it is through this framework that he will be able to organize pedagogical actions aimed at the development of competences/abilities provided for by the BNCC , with a view to the integral formation of the student”. In the search for these understandings, interviews were carried out with Mathematics teachers working in High School with the objective of identifying the articulation between the teachers' knowledge and the BNCC; relate actions developed during practices involving digital technologies and point out possible pedagogical actions that can contribute to the advancement of learning in Mathematics, as well as analyze how the PCK of these teachers contemplate the competences/abilities predicted by the base. Among the results obtained, it is highlighted that teachers who show understanding and who have ownership over the knowledge that organize their PCK organize better pedagogical actions with purposes compatible with what is foreseen in the base document, such as actions that allow students to interact with colleagues and teachers, investigating, explaining and justifying possible solutions to problems and thus giving emphasis to the construction of mathematical argumentation. However, it is possible to evidence that the elements presented in the pedagogical practices and that compose and organize the knowledge of the PCK contemplate the competences/abilities foreseen in the BNCC with regard to the understanding of the process as a whole, as they direct to the integrality of Mathematics as an area and seek to develop questions that can induce the student to understand the different situations that they may experience in everyday life.